Characterizing Aqueous Foams by In Situ Viscosity Measurement in a Foam Column - Yu, Wei (Langmuir : the ACS journal of surfaces and colloids, 2023)
Foam characterization is essential in many applications of foams, such as cleaning, food processing, cosmetics, and oil production, due to these applications' diversified requirements. The standard characterization method, the foam column test, cannot provide sufficient information for in-depth studies. Hence, there have been many studies that incorporated different characterization methods into a standard test. It should be enlightening and feasible to measure the foam viscosity, which is both of practical and fundamental interest during the foam column test, but it has never been done before. Here, we demonstrate a method to characterize aqueous foams and their aging behaviors with the simultaneous measurement of foam viscosity and foam height. Using a vibration viscometer, we integrate foam column experiments with in situ foam viscosity measurements. We studied the correlation among the foam structure, foam height, and foam viscosity during the foam decay process. We found a drastic decrease in foam viscosity in the early foam decay, while the foam height remained unchanged, which is explained by coarsening. This method is much more sensitive and time-efficient than conventional foam-height-based methods by comparing the half-life. This method successfully characterizes the stability of foams made of various combinations of surfactants and gases